Secondary Immobilization as a Phase of N mineralization Dynamics of Soil Organic Inputs - Panagiotis Dalias; Anastasis Christou (Nitrogen, 2022)
Current understanding of nitrogen (N) mineralization from organic soil inputs considers three alternative processes: immediate net mineralization of N, net immobilization followed by net mineralization, or exclusively net immobilization. The three processes are compatible and linked with the C:N ratio rule. However, research evidence from a number of incubation studies incorporating processed materials like manures, composts, manure composts, or already decomposed plant residues suggest the presence of a second N immobilization phase. The mechanisms and conditions of this process, which is against the prevailing theory of soil N cycling, have not been ascertained, but they should most likely be attributed to impeded dead microbial biomass turnover. The transfer of mineral forms of N to the organic N pool may reasonably be explained by the chemical stabilization of nitrogenous compounds with secondary products of lignin degradation, which occurs late after incorporation of an organic input in soil. Secondary immobilization questions the reliability of the C:N ratio and most likely of other quality indices if proved to be real, even to some extent, while it may also have significant consequences on the management of soil organic additives applied as fertilizers.